Toll-Like Receptor 4 as a Favorable Prognostic Marker in Bladder Cancer: A Multi-Omics Analysis - Lu, Jun-Lin; Xia, Qi-Dong; Sun, Yi; Xun, Yang; Hu, Heng-Long; Liu, Chen-Qian; Sun, Jian-Xuan; Xu, Jin-Zhou; Hu, Jia; Wang, Shao-Gang (Frontiers in Cell and Developmental Biology, 2021)
Background: The toll-like receptor 4 (TLR4) agonist, Bacille Calmette-Guérin (BCG), has exhibited gratifying effects in treating bladder cancer. The study aims to explore the expression pattern, prognostic value, and potential mechanism of TLR4 in bladder cancer. Methods: The transcriptome file from the GSE13507 dataset in the GEO database and the promoter methylation file from bladder cancer dataset in the TCGA database were downloaded for analysis. The prognostic value of TLRs was assessed by univariate cox regression. Immunohistochemistry was applied to verify the expression of TLR4 in bladder cancer. The drug response is estimated through the R package “pRRophetic”. The CIBERSORT algorithm was carried out to estimate the infiltrating immune cells of samples. Gene set enrichment analysis (GSEA) was performed to identify involving pathways under varied TLR4 expression levels. Results: TLR4 is significantly decreased in tumor tissues compared to surrounding tumor tissues or normal tissue, which is also positively correlated to the overall survival rate (hazard ratio [HR]=0.38) and cancer specific survival rate (HR=0.15) of patients with bladder cancer. Low expression of TLR4 is observed in tumors with malignant performance (high pathological grade, higher tumor stage, and progression). Patients with low TLR4 level are more sensitive to gemcitabine rather than cisplatin. The promoter methylation level of TLR4 is positively associated with TLR4 expression (P < 0.001). The cg14629571 methylation site largely contributes to the overall methylation level. The CIBERSORT analysis shows that high TLR4 expression is associated with lower plasma cell, M0 macrophage, and M1 macrophage. The GSEA results indicate that the TGF-β pathway and apoptosis are activated in high TLR4 bladder cancer, while G2M checkpoint and E2F targets pathways are enriched in low TLR4 bladder cancer. Conclusions: The research depicts the abnormal expression and prognostic value of TLR4 in bladder cancer. The TLR4 expression can effectively predict oncological outcomes and drug sensitivity of bladder cancer patients. TLR4 is also associated with infiltrating immune cell variation and cancer pathway dysregulation. The results provide a novel prognostic marker and potential drug targets for bladder cancer.